Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

This problem appears to be pretty simple to me but my book gets a different answer.

$$\frac{dy}{dx} = xy^2$$ For when y is not 0 $$\frac{dy}{y^2} = x \, dx$$ $$\int \frac{dy}{y^2} = \int x \, dx$$

$$\frac{-1}{y^1} = \frac{x^2}{2}$$

$$\frac{-2}{x^2} = y$$

Is there anything wrong with this solution? It is not what my book gets but it is similar to how they do it in the example.

share|cite|improve this question
You're only missing a constant of integration $C$. An initial condition $f(a)=b$ will give it a value. Meanwhile, it has to be there. – Pedro Tamaroff Jun 14 '12 at 19:56
My book gets $\frac{2}{K - x^2}$ and $y=0$ – user138246 Jun 14 '12 at 19:57
The first nice thing about an explicit solution of an ODE is that you can easily differentiate the result and see whether it fulfills the equation. The second nice thing are well known uniqueness results for boundary value problems of ODE, which often tell you that if you have a solution it it is the only one. – user20266 Jun 14 '12 at 19:58
Well, see that $$-\frac{1} y=\frac{x^2}{2}+K$$ Now solve for $y$. – Pedro Tamaroff Jun 14 '12 at 19:59
Note that dividing by $y^2$ is not valid if our function $y$ is identically $0$. And indeed $y$ identically $0$ is a solution of the DE. – André Nicolas Jun 14 '12 at 20:21
up vote 2 down vote accepted

When you apply indefinite integration, you need to add a "${}+C\,$" (or whatever letter you want) at the end; this is rather infamous for tripping up students. In your problem this gives

$$-\frac{1}{y}=\frac{x^2}{2}+C~~\implies~~ y=\frac{1}{-(x^2/2+C)}=\frac{2}{-x^2-2C}.$$

If we write $K=-2C$ (or again, any old letter), we can write this simply as $\displaystyle\frac{2}{K-x^2}$.

The reason we have "plus a constant" at the end is to prevent erroneous derivations like this:

$$\frac{d}{dx}f(x)=\frac{d}{dx}\big(f(x)+1\big)\implies f(x)=f(x)+1\implies 0=1.$$

In other words, antidifferentiation will only find the antiderivative you want up to addition by an unknown constant. (However with some initial conditions this constant, or constants as it may be in more complicated problems, may be computed exactly.)

Note that it is only necessary to write an add-a-constant to one side of an equation, because for example something like $f(x)+A=g(x)+B$ can be written instead as $f(x)=g(x)+C$ with our constant $C=B-A$.

share|cite|improve this answer

Your mistake is here. You should have $$\int \frac{dy}{y^2} = \int y^{-2}dy = -y^{-1}$$ and not $$\int \frac{dy}{y^2} = \frac{-1}{y^{-1}}$$.

share|cite|improve this answer
It looks like that was just a typo on the op's part.. – Court Jun 14 '12 at 19:59
No, I don't think so. – Old John Jun 14 '12 at 20:00
That was a typo, I fixed it. – user138246 Jun 14 '12 at 20:01
I do think so. Mull over the last line in the OP's derivation. (Also Jordan edited while I was typing.) – anon Jun 14 '12 at 20:01
OK - it was a typo – Old John Jun 14 '12 at 20:03

Continuing from what you did, we have

$$\int \frac{dy}{y^2} = \int x\,dx$$

$$-\frac{1}{y} + C_2= \frac{x^2}{2}+C_1$$

Where $C_1$ and $C_2$ are constants of integration. Letting $C_3=C_1-C_2$

$$-\frac{1}{y} + C_2= \frac{x^2}{2}+C_1=-\frac{1}{y}= \frac{x^2}{2}+C_3$$

Solving for $y$, we have:

$$-\frac{1}{y}= \frac{x^2}{2}+C_3= \frac{x^2+2C_3}{2} \implies -y=\frac{2}{x^2+2C_3} \\ \implies y=\frac{2}{2C_3-x^2}$$

Letting $2C_3=K$


share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.